Association of Life's Simple 7 with incident dementia and its modification by the apolipoprotein E genotype. Issue 12 (2nd May 2021) - Guo, Jing; Brickman, Adam M.; Manly, Jennifer J.; Reitz, Christiane; Schupf, Nicole; Mayeux, Richard P.; Gu, Yian
Abstract: Introduction: There is limited and inconsistent reporting on the association between Life's Simple 7 (LS7) and dementia in the elderly population. Methods: Based on the Washington Heights‐Inwood Columbia Aging Project (WHICAP), LS7 scores were estimated to assess cardiovascular health status. Associations between LS7 scores and incident dementia were investigated by Cox proportional hazards models. Results: Among 1987 subjects, 291 incident cases of dementia were identified over a median follow‐up of 5.84 years. Compared with subjects in the poor cardiovascular health group (scores 0 to 5), those in intermediate (6 to 9) and optimal (10 to 14) groups had lower dementia risk, with the hazard ratio (HR; 95% confidence interval) being 0.74 (0.54 to 1.00) and 0.59 (0.38 to 0.91), respectively. These results were significant in apolipoprotein E genotype ε4 ( APOE ε4) allele non‐carriers but not in carriers. Discussion: Higher LS7 scores are protective for dementia, especially among the APOE ε4 noncarriers.